4th International Triennial Ecology and Art : Art d'Eco. - 4th International Triennial Ecology and Art, Maribor (Maribor : Umetnostna Galerija, 1992)
Bielz, Gudrun ; Hoffmann, Peter G. ; Schatz, Gebhard ; van der Straeten, Andrea ; Wid, Udo ; Faktor, Ivan ; Ivancic, Pino ; Kozaric, Ivan ; Pokas, Vesna ; Cucchi, enzo ; Gilardi, Piero ; Kounellis, Jannis ; Merz, Mario ; Mochetti, Maurizio ; Paolini, Gulio ; Plessi, Fabrizio ; Kirbis, Dusan ; Lenardic, Zmago ; Pogacar, Tadej ; Prosenc, Natasa ; Cervek, Sandi ; Jerkovic, Zdravko ; Rimele, Oto ; Stokelj, Bojan
4th International Triennial Ecology and Art, Umetnostna Galerija, Maribor, 19. VI. - 31. VII. 1992
boek
Keywords: Oostenrijk; Kroatië; Italië; Slovenië